The presidency as a task. The image of Poland’s presidency of the Council of the European Union in selected Polish weekly magazines - Lipiński, Artur (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Despite the fact that it is exercised in the interests of the European Union as a whole, the presidency of the Council of the European Union is also an excellent opportunity to promote national interests and a positive image of the country, acting as an ‘amplifier’ of the voice of the state. Particular significance should be ascribed to the European and national media, which can support the positive image of a specific country and its government, but can also undermine such an image. The purpose of this paper is to raise the question of the specific mechanisms of constructing the image of Poland, Europe/European Union and the Polish presidency in the national media. The paper also indicates the mechanisms for building support for the vision of the Polish government, the European Union and the Polish presidency. The theoretical foundations of this article are provided by the analytical categories and concepts developed by critical discourse analysis. The article examines how the media represented individual and collective political actors, attributed specific characteristics to them, and used arguments in favor of a particular vision of Poland, the European Union and the Polish presidency of the EU Council.